The transition of worker to formality: evidences from duration analysis - Romanello, Michele; de Oliveira Gonçalves, Flávio (Economía Sociedad y Territorio, 2017)
This paper aims to evidence the characteristics of individuals that affect more the transition from informal to formal sector. The initial hypothesis is that the level of education of each individual is the most important characteristic explaining this transition. To achieve this purpose, we utilize parametric and non-parametric survival analysis: through the hazard function, it was possible to investigate what factors affect the risk of transiting to formality for a worker. For this analysis, we use the data from the Monthly Employment Survey (PME). The level of education appears to be the main characteristic that explains the exit of workers from informality.